Prevalence and risk factors of PTSD symptoms: a 3-month follow-up study - Zhilei Shang; Xiao Pan; Suhui Cheng; Yuchen Yang; Wenjie Yan; LiangLiang Sun; Hai Huang; Yonghai Bai; Weifen Xie; Shu Xu (SAGE Publishing, 2024)
Background: During the peak of the epidemic, hospitalized patients frequently encountered significant health risks and potentially life-threatening circumstances, including uncertainty regarding treatment and the potential for complications. Objective: The present study aimed to explore the prevalence of post-traumatic stress disorder (PTSD) symptoms among hospitalized patients 3 months after discharge during the first peak of the epidemic, and the association of PTSD with disease-related characteristics. Design: A single-center and full-sample follow-up study was conducted on COVID-19 patients from the Optical Valley Branch of Maternal and Child Hospital of Hubei Province, Wuhan, China. Data were collected during their hospitalization and 3 months after discharge. Methods: PTSD symptoms were evaluated by primary care post-traumatic stress disorder (PC-PTSD), a total score of 3 or above was considered as clinically significant PTSD symptoms. Demographic and disease-related characteristics were collected to identify related associations with PTSD symptoms. Results: A total of 903 patients completed the follow-up survey, yielding a response rate of 63.5%. A total of 212 (23.5%) of the patients were positive in PC-PTSD screening. Univariate regression analysis identified several factors correlated with PTSD symptoms, including female gender, younger age, a lower body mass index (BMI), preexisting sleep problems, bereavement due to COVID-19, a severe clinical diagnosis, the presence of three or more clinical symptoms at disease onset, and residual respiratory symptoms after discharge. Notably, in the multivariate regression analysis, experiencing three or more clinical symptoms at onset emerged as a robust predictor of PTSD symptoms (OR = 2.09, 95% CI: 1.48-2.95). An intriguing finding was that patients who underwent radiological assessment post-discharge reported a higher incidence of PTSD symptoms, whereas those who underwent re-testing for IgG or IgM antibodies exhibited a lower prevalence of PTSD symptoms. Conclusion: Three months post-recovery, PTSD symptoms prevalence among COVID-19 patients was 23.5%. Those with three or more clinical symptoms at onset or residual respiratory symptoms post-discharge showed higher risk. These findings highlighted the long-term effect of COVID-19 on mental health, urging enhanced attention and interventions for survivors.